Indian values in Asia - Dang, Van Thang (VNU - HCM, 2016)
Flexibility in India's foreign policy the important foundation for Indian's development from mid- twentieth century to the early of twenty - first century; the dramatic transformation of VietNam - Indian trade relations in the early twenty first century...